Determining water storage depletion within Iran by assimilating GRACE data into the W3RA hydrological model. (April 2018) - Khaki, M.; Forootan, E.; Kuhn, M.; Awange, J.; van Dijk, A.I.J.M.; Schumacher, M.; Sharifi, M.A.
Highlights: We assimilate GRACE data to improve a hydrological model estimations over Iran. Ensemble Square-Root Filter is used for data assimilation. We estimate sub-surface water storage changes within the country. Climate and anthropogenic impacts on the water storages are investigated. Independent in-situ measurements are used to evaluate the results. Abstract: Groundwater depletion, due to both unsustainable water use and a decrease in precipitation, has been reported in many parts of Iran. In order to analyze these changes during the recent decade, in this study, we assimilate Terrestrial Water Storage (TWS) data from the Gravity Recovery And Climate Experiment (GRACE) into the World-Wide Water Resources Assessment (W3RA) model. This assimilation improves model derived water storage simulations by introducing missing trends and correcting the amplitude and phase of seasonal water storage variations. The Ensemble Square-Root Filter (EnSRF) technique is applied, which showed stable performance in propagating errors during the assimilation period (2002–2012). Our focus is on sub-surface water storage changes including groundwater and soil moisture variations within six major drainage divisions covering the whole Iran including its eastern part (East), Caspian Sea, Centre, Sarakhs, Persian Gulf and Oman Sea, and Lake Urmia. Results indicate an average of -8.9 mm/year groundwater reduction within Iran during the period 2002 to 2012. A similar decrease is also observed in soil moisture storage especially after 2005. We further apply the canonical correlation analysis (CCA) technique to relate sub-surface water storage changes to climate (e.g., precipitation) and anthropogenic (e.g., farming) impacts. Results indicate an average correlation of 0.81 between rainfall and groundwater variations and also a large impact of anthropogenic activities (mainly for irrigations) on Iran's water storage depletions.